Oceanography north of 60°N from World Ocean Database. (March 2015) - Seidov, D.; Antonov, J.I.; Arzayus, K.M.; Baranova, O.K.; Biddle, M.; Boyer, T.P.; Johnson, D.R.; Mishonov, A.V.; Paver, C.; Zweng, M.M.
Highlights: Variability of the ocean north of 60°N is investigated on decadal time scales. We use new high-resolution regional climatologies to track ocean variability. We document the complex spatial distribution of ocean warming and cooling. Correlation of ocean variability with two major climate indices is investigated. Abstract: The National Oceanographic Data Center (NODC) has produced high-resolution regional ocean climatologies that reveal much greater detail than previously available in selected regions. A pilot study based on the NODC Arctic Regional Climatology (ARC) was carried out to track multidecadal ocean climate variability of the oceans and seas north of 60°N (referred to as Northern Waters). The structure and data coverage for the Northern Waters provided by this climatology are discussed. Multidecadal variability of the Northern Waters is analyzed with one- and quarter-degree resolutions. Our analysis indicates that although the Northern Waters are warming as a whole, the overall climatic trend and spatial distribution of warming and cooling areas are rather intricate and patchy, with some areas even having intermittent cooling episodes. Complex relations of the upper ocean warming and two major climate indices—the Atlantic Multidecadal Oscillation (AMO) and North Atlantic Oscillation (NAO)—are discussed based on new ocean heat content calculations for the Greenland–Norwegian–Iceland Seas (GINS) and Arctic Ocean. Preliminary estimates suggest that multidecadal variability in the Northern Waters is more closely correlated with the AMO than the NAO, especially in the GINS.